A matched case–control study of the clinical, economic, and patient-reported outcomes of cystoid macular edema complicating phacoemulsification surgery. Issue 6 (June 2020) - Sanders, Francis W.B.; Lowin, Peta; Gupta, Nitin; Roberts, Harry W.
Abstract : Patients with pseudophakic macular edema reported worse visual impairment compared with control subjects, and a significant proportion of cases were refractory to standard therapeutic interventions and incurred significant cost to the NHS. Abstract : Purpose: To assess the visual outcomes of pseudophakic cystoid macular edema (CME) as compared with age- and copathology-matched control subjects, the costs of treatment and follow-up, and the patient-reported outcomes using the new Cat-patient-reported outcome measures (PROM) 5 questionnaire. Setting: West Suffolk Hospital NHS Foundation Trust, United Kingdom. Design: Matched case–control study. Methods: Fifty-two eyes of 49 patients developed CME over an 18-month period. Age- and copathology-matched patients were identified from clinical records over the same time period in a 2:1 ratio (90 eyes). Postoperative clinical outcomes were recorded including treatments received, costs of treatments, and patient-reported outcome measures using the Cat-PROM5. Results: Patients with CME reported a significantly worse outcome from surgery than control subjects. Furthermore, patients with CME had significantly worse visual acuity postoperatively than control subjects (CME: logarithm of the minimum angle of resolution 0.40 ± 0.33, n = 37; control subjects: 0.30 ± 0.33; P < .05) despite there being no difference in preoperative visual acuity. In patients with epiretinal membrane (ERM), notably those with CME had worse patient-reported outcomes than control subjects with ERM, and only 18% received prophylactic corticosteroid injection at surgery compared with 63.6% of control subjects. CME resulted in an excess of 266 outpatient appointments, with 388 weeks of topical therapy, 18 orbital floor injections, 6 intravitreal steroid injections, 5 intravitreal antivascular endothelial growth factor injections, and 1 intravitreal dexamethasone implant with an excess expenditure of £216.81 per case. Conclusions: Patients developing CME after cataract surgery had reduced visual acuity at 4 to 6 weeks, patient-reported visual outcomes, and increased number of hospital appointments, treatments, and costs.